Performance Measurement Based on Coloured Petri Net Simulation of Scalable Business Processes - Abd. Charis Fauzan; Riyanarto Sarno; Muhammad Ainul Yaqin (IAES Indonesia Section, 2017)
Business process is also a complex area which receives much attention in recent years especially in increasing productivity and saving cost. Meanwhile, situation at the company allows existing business processes to be enlarged. This paper proposed the performance measurement based on coloured petri net simulation of scalable business processes, which has purpose to compare the performance of scalable business processes. For experiments, this paper uses real-world business processes. Then compare it to some business processes that have been enlarged. The result shows that scalable business processes influence the performance of business process. This paper provides feedback to business process developers for determine appropriate business processes based on the performance through coloured petri net simulation.